Single Spine, Double Spine or Multiple Spine: Solving Labour Conflicts and Making Public Sector Jobs More Rewarding in Ghana - Isaac Brako; Kwame Asah-Asante (Modern Africa, 2014)
The governments of Ghana and public sector workers have  since the country’s independence, well over fifty years ago, been  embroiled in a protracted fisticuff all in their quest for a rewarding  compensation package that will adequately recompense the latter  for the physical and mental efforts they exert at their various places  of work. The road to finding a lasting solution to this brawl has been  tortuous, bumpy and chequered.  Commissions upon commissions have been instituted to among other  issues, advise the government on the effective ways of rewarding the  country’s labour to stem the tide of labour agitations for an enhanced,  equitable and rewarding compensation regime, but this single laudable  objective has never been attained.  Incessant strikes, threats of strikes and storms of protests continue  to greet every government that assumes political power in Ghana.  Hardly a year goes passed without a group of labour unions issuing  such threats or embarking upon work stoppage either to demonstrate  their dissatisfaction with government’s lackadaisical attitude to the  implementation of one public sector salary regime or to demand for  enhanced remuneration package.  The real solution to this age-long problem continues to elude the  country. The single-spine pay policy (SSPP), which was touted to be a  panacea for the craved for rewarding compensation by Ghana labour  has failed to suffice to whet the appetite of public sector workers. So,  where do we turn next?  This paper traces various attempts both past and present governments  have made to find a lasting solution to the protracted labour agitations  for enhanced remuneration for a comprehensive, equitable and  rewarding compensation package for the public sector workers in  Ghana. It enquires into other possible measures of solving the matrices of confronting the onslaught in the labour front to stem the tide of agitations over wages and salaries. The data was obtained from both primary and secondary sources. The primary data comprises of reports by commissions and committees set up to review wages and salaries for the country’s public sector which is supported with information from existing literature on the subject.